The Impact of SEC Disclosure Monitoring on the Uncertainty of Fair Value Estimates - Bens, Daniel A.; Cheng, Mei; Neamtiu, Monica (The Accounting Review, 2016)
ABSTRACT We investigate the role played by the Securities and Exchange Commission (SEC) in monitoring fair value disclosures in regulatory filings. Specifically, we assess whether SEC action via the issuance of fair value comment letters to registrants is followed by reductions in uncertainty about the firms' fair value estimates. We hypothesize that registrants that receive a comment letter focusing on their fair value disclosure policies experience reductions in investor uncertainty regarding their fair value estimates in the post-letter period, compared to the pre-letter period. Supporting this prediction, we find that for the periods after the fair value comment letters, the associations between Level 2 and 3 fair value assets and our measures of uncertainty are significantly reduced. These findings are robust to a series of tests designed to ensure that we do not simply capture general changes in market uncertainty levels for firms investing in these types of assets. Our study contributes to the further understanding of market participants' perception of fair value disclosures by investigating the role of SEC enforcement. This finding is important given recent criticisms of fair value reporting emanating from the highest levels of government and industry. Data Availability: Data are available from public sources identified in the paper.